GAA variants and phenotypes among 1, 079 patients with Pompe disease: Data from the Pompe Registry. Issue 11 (7th August 2019) - Reuser, Arnold J. J.; van der Ploeg, Ans T.; Chien, Yin‐Hsiu; Llerena, Juan; Abbott, Mary‐Alice; Clemens, Paula R.; Kimonis, Virginia E.; Leslie, Nancy; Maruti, Sonia S.; Sanson, Bernd‐Jan; Araujo, Roberto; Periquet, Magali; et al.
Abstract: Identification of variants in the acid α‐glucosidase ( GAA ) gene in Pompe disease provides valuable insights and systematic overviews are needed. We report on the number, nature, frequency, and geographic distribution of GAA sequence variants listed in the Pompe Registry, a long‐term, observational program and the largest global repository of Pompe disease data. Variant information was reviewed and compared with publicly available GAA databases/resources. Among 1, 079 eligible patients, 2, 075 GAA variants (80 unique novel) were reported. Variants were listed by groups representing Pompe disease phenotypes. Patients were classified as Group A: Symptom onset ≤ 12 months of age with cardiomyopathy; Group B: Symptom onset ≤ 12 years of age (includes patients with symptom onset ≤ 12 months of age without cardiomyopathy); or Group C: Symptom onset > 12 years of age. Likely impact of novel variants was predicted using bioinformatics algorithms. Variants were classified by pathogenicity using ACMG guidelines. Data reported from the Pompe Registry provide new information about the distribution of GAA variants globally and across the clinical spectrum, add to the number and diversity of GAA variants registered in public databases through published data sharing, provide a first indication of the severity of novel variants, and assist in diagnostic practice and outcome prediction.